The Obstacles and Challenges of Islamic Banking Inclusion in Banking Digitalization in the Era of Financial Technology (Fintech) - Yusiresita Pajaria (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2025)
This study aims to find out and examine what are the Barriers and Challenges of Islamic Banking Inclusion in the Digitalization of Banking in the Era of Financial Technology (FINTECH).The research method used isdata collection methods through library research.using qualitative analysis, which means describing the data processed in detail in the form of sentences (descriptive). Qualitative analysis is carried out starting from empirical analysis, which in its deepening is complemented by normative analysis.To analyze the data, the three methods of data analysis used are inductive, deductive, and comparative methods. The research results areThe development of Islamic banking has several shortcomings such as: vision, capital, products, financing, human resources (HR), services, information, public understanding; FINTECH's presence influences Islamic banking, namely contributing such as: easy and inexpensive services as well as effective and efficient, helping Islamic banks in the speed and accuracy in processing business operations and product marketing data, providingsignificant impact on several aspects of the economy, while at the same time rearranging the face of the Islamic financial industry,rapid developmentFINTECHdirectly proportional to the challenges faced,a driver for achieving financial inclusion, the presence of a strong consumer protection system and digital ecosystem, FINTECH Islamic banking with massive development in Indonesia, FINTECH and banjs wil collaborate together. Keywords: Financial Technology, Digitalization of Islamic Banking, Financial Inclusion